Malate Oxidation and Cyanide-Insensitive Respiration in Avocado Mitochondria during the Climacteric Cycle - Moreau, Francois (1982)
After preparation on self-generated Percoll gradients, avocado (Persea americana Mill, var. Fuerte and Hass) mitochondria retain a high proportion of cyanide-insensitive respiration, especially with α-ketoglutarate and malate as substrates. Whereas α-ketoglutarate oxidation remains unchanged, the rate of malate oxidation increases as ripening advances through the climacteric. An enhancement of mitochondrial malic enzyme activity, measured by the accumulation of pyruvate, closely parallels the increase of malate oxidation. The capacity for cyanide-insensitive respiration is also considerably enhanced while respiratory control decreases (from 3.3 to 1.7), leading to high state 4 rates. Both malate dehydrogenase and malic enzyme are functional in state 3, but malic enzyme appears to predominate before the addition of ADP and after its depletion. In the presence of cyanide, a membrane potential is generated when the alterntive pathway is operating. Cyanide-insensitive malate oxidation can be either coupled to the first phosphorylation site, sensitive to rotenone, or by-pass this site. In the absence of phosphate acceptor, malate oxidation is mainly carried out via malic enzyme and the alternative pathway. Experimental modification of the external mitochondrial environment in vitro (pH, NAD(+), glutamade) results in changes in malate dehydrogenase and malic enzyme activities, which also modify cyanide resistance. It appears that a functional connection exists between malic enzyme and the alternative pathway via a rotenone-insensitive NADH dehydrogenase and that this pathway is responsible, in part, for nonphosphorylating respiratory activity during the climacteric.